The new politics of strategic resources : energy and food securit y challenges in the 21st century - Steven, David, 1968- (Washington, D.C. : Brookings Institution Press, 2014)
"Examines the political dimensions of strategic resource challenges at the domestic and international levels, including energy and food mar kets, water scarcity, and the roles of various actors such as the U.S., China, India, Russia, Saudi Arabia, and others"--
Acknowledgments -- Introduction: energy policy on the edge / Bruce J ones and David Steven -- The rising actors -- China's search for oil se curity : a critique / Andrew B. Kennedy, Senior Lecturer, Australian Na tional University -- Materials, markets, multilateralism : a strategic approach to India's resource challenges / David Steven and Arunabha Gho sh, CEO of the Council on Energy, Environment and Water -- Brazil's pri ncipled pragmatism : a viable response to the new geopolitics of resour ce competition? / Antonio Ramalho, Professor, University of Brasâilia - - The big squeeze : Nigeria on the brink / Mark Weston, Policy Consulta nt, Riverpath Associates -- Facets of resource security -- Routes to en ergy security : the geopolitics of gas pipelines between the EU and its southeastern neighbors / Angel Saz-Carranza and Marie Vandendriessche -- Energy rivalry between India and China : less than meets the eye? / C. Raja Mohan, Head of Strategic Studies, Observer Research Foundation, New Delhi, and Lydia Powell, Head, Centre for Resources Management, Ob server Research Foundation, New Delhi -- Resource security in Saudi Ara bia : domestic challenges and global implications / Kristian Coates Ulr ichsen, Research Fellow, Department of Governance, London School of Eco nomics -- Governance for a resilient food system / Alexander Evans, Sen ior Fellow, NYU CIC -- Water security : global implications and respons es / Daniel Kim Chai Yeo, Fellow, WaterAid -- Oil, domestic politics, a nd international conflict / Jeff D. Colgan, Brown University -- Russia gambles on resource scarcity : energy intrigues in a time of political crisis / Pavel K. Baev, Research Professor, PRIO -- The critical actor -- Challenges to sustainable growth after the Great Recession : how Ame rica can lead / Joshua Meltzer, David Steven, and Claire Langley -- Gov ernance burdens and the role of the United States in the new energy lan dscape / Kevin Massy, Fellow, Brookings Institution -- Contributors -- Index.
Includes bibliographical references and index.
Keywords: Energy policy; Food security; Natural resources -- Management